2018
DOI: 10.1039/c8cs00253c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activations of unstrained C–C bond involving organometallic intermediates

Abstract: The cleavage of C-C bonds has been a great challenge owing to their thermodynamic and kinetic stability. To date, the progress made in this area has mainly relied on the reaction of small rings, which is driven by releasing ring strain. Encouragingly, more and more examples of the cleavage of non-strained C-C bonds have been reported. This review provides a comprehensive overview of the transition-metal-catalyzed C-C bond activation of relatively stable and unstrained molecules that involves the formation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(109 citation statements)
references
References 150 publications
2
107
0
Order By: Relevance
“…However, transition‐metal catalyzed C−C bond cleavage is challenging. For example, C−C bond activation of secondary alcohols faces two challenges: (i) β‐H elimination of metal‐alcoholate is often preferred over β‐C elimination owing to higher stability of M−H bond, which makes C−C bond cleavage thermodynamically disfavored; (ii) secondary alcohols could be easily converted to ketones under oxidative conditions (Scheme ) . Despite the challenges of this field, various significant studies have been reported, such as those by Shi, Kang, Yin and Morandi .…”
Section: Methodsmentioning
confidence: 99%
“…However, transition‐metal catalyzed C−C bond cleavage is challenging. For example, C−C bond activation of secondary alcohols faces two challenges: (i) β‐H elimination of metal‐alcoholate is often preferred over β‐C elimination owing to higher stability of M−H bond, which makes C−C bond cleavage thermodynamically disfavored; (ii) secondary alcohols could be easily converted to ketones under oxidative conditions (Scheme ) . Despite the challenges of this field, various significant studies have been reported, such as those by Shi, Kang, Yin and Morandi .…”
Section: Methodsmentioning
confidence: 99%
“…A great variety of N-tosylhydrazones and disulfides were successfully converted into the corresponding dithioacetals in moderate to good yields. C−C bond fragmentation is a useful method to provide a fragment for the functionalization of molecules and has been extensively applied in organic synthesis [19]. In recent years, C-C bond cleavage/sulfenylation reactions via radical pathways have emerged as a practical tool for the synthesis of aryl alkyl sulfides [20].…”
Section: Scheme 1 C-s Coupling Reaction Of Diazo Compounds and Disulmentioning
confidence: 99%
“…Inthe past decade,c atalytic CÀCb ond activation has received increasing attention, allowing facile reconstruction and reorganization of carbon skeletons. [1] TheC À Cb ond activation is typically fulfilled through two elementary,n onradical reaction pathways,namely the CÀCoxidative addition and b-carbon elimination. [1] Despite the advancement, the majority of reported systems rely on noble metal catalysis.…”
mentioning
confidence: 99%
“…[1] TheC À Cb ond activation is typically fulfilled through two elementary,n onradical reaction pathways,namely the CÀCoxidative addition and b-carbon elimination. [1] Despite the advancement, the majority of reported systems rely on noble metal catalysis. [2][3][4] In addition, the development of asymmetric catalytic C À C bond activation systems severely lags behind, [5,6] even for activated C À Cb onds,a nd previously reported systems are predominantly initiated by chelation-assisted CÀCb ond oxidative addition, followed by intramolecular insertion into aC =C, C=O, or C=Nbond (Schemes 1a).…”
mentioning
confidence: 99%